La ‘Nembo’ a Filottrano - Carmelo Burgio (Nuova Antologia Militare)
The analysis of the operations of the Nembo airborne division, when it depended on the Italian Liberation Corps, focusing on the Filottrano fighting. It was the first true victory of the Italian units in a major fighting during the Liberation Campaign. It was obtained employing national weapons and equipment: this success was extremely decisive to convince the Allies to allow the Italian co-belligerent authorities to give a bigger contribution in the war against Germany.